Methods of Promoting Learning and Data Quality in Citizen and Community Science - Herodotou, Christothea; Scanlon, Eileen; Sharples, Mike (Frontiers in Climate, 2021)
Citizen science or community science (CS) programmes are engaging volunteers in specific stages of the scientific research, mostly data collection and processing. They are less likely to have an explicit objective to support and promote volunteers’ learning. In response to that, ‘citizen inquiry’ emphases citizens’ learning and community education, by viewing CS as an opportunity to educate the general public in thinking and acting scientifically. In citizen inquiry, citizens can take part in all the stages of the scientific research, from setting up an inquiry of personal interest, to deciding on the methods of data collection, analysis and reporting. To ensure data quality when non-professionals design their own or take part in existing investigations, we have designed a bespoke online technological solution, the nQuire platform (nquire.org.uk), with support from the BBC. nQuire scaffolds the design of high quality scientific inquiries through an authoring functionality and a process of data quality review by experts. In this paper, we detail how nQuire can support data quality assurance and control. We present case studies of how data quality was managed in two projects: “Heatwaves: Are you coping?” and “Pollinator Watch”.